The taxamycins: A new family of enediyne compounds. - Harwig, Curtis W. (University of Ottawa (Canada), 1997)
The enediyne antibiotics have generated widespread interest due to their novel mechanism of DNA cleavage and the synthetic challenge these structures represent. Similarly, considerable effort is being devoted to the study of the structurally complex and potent antitumour agent, Taxol$\sp\circler.$ This thesis describes the preparation of a new family of compounds, the "taxamycins", which contain important features from both types of natural products. The synthesis and functionalization of the 10-, 11- and 12-membered, bicyclic ring taxamycin adducts 290, 270 and 240a respectively, are described. The construction of several models was first examined using the enediyne synthon 176. The building block 177 was prepared by two successive Pd(0)-based couplings followed by selective removal of the trimethylsilyl group. The lithiated derivative of 177 was condensed onto several carbonyl-containing precursors (182, 204 and 212) to synthesize 10- and 11-membered bicyclic enediyne systems but, in each case, final ring closure could not be effected under various reaction conditions. Thus, attention was directed towards the Taxol$\sp\circler$ A ring analogue 245, prepared efficiently in 5 steps from the commercially available 2,3-dimethyl-2-butene (overall yield of 22%). Enediyne 177 was condensed stereoselectively onto precursor 245 and elaborated to iodoaldehyde 239. The final cyclization to the taxamycin-12 model 240a was achieved stereoselectively by intramolecular Cr(II)-Ni(II) mediated Nozaki-Kishi condensation of 239 in variable yield (7-60%). The Bergman cycloaromatization of 240a provided the tricyclic, taxane nucleus in low yield. A similar approach, using the A ring compound 263, was employed in the preparation of the taxamycin-11 adduct 270. The Nozaki-Kishi coupling of iodoaldehyde 269 afforded 270 in low to modest yield (7-37%). Intramolecular acetylide condensation of aldehyde 271 also effected ring closure in low yield (15-25%). The preparation of the 10-membered ring model 290 completed the taxamycin series. The gem dimethyl group was omitted in this model to obtain higher yields of cyclization compared to the preceding examples. Preparation of taxamycin-10 290 was accomplished by addition and subsequent elaboration of synthon 177 to precursor 283. The final ring closure was effected stereoselectively by intramolecular Cr(II)-mediated Nozaki-Kishi coupling or by intramolecular anionic cyclization in good yields (60-76%). Further derivatization of 291 by SeO$\sb2$ allylic oxidation was successful and allowed for the attachment of the Taxotere$\sp\circler$ side chain. The resolution of the racemic taxamycin-10 adduct was accomplished by introduction of this enantiomerically enriched side chain and provided derivatives 300a and 300b. Currently, the biological activity of these and related enantiomeric adducts is being investigated. Preliminary attempts to induce Bergman cycloaromatization of taxamycin-10 were also examined, via introduction of different triggering devices at the C-8 hydroxyl position.* ftn*Please refer to the dissertation for diagrams.
Keywords: Chemistry, Organic.